A modified technique for reconstruction of a total maxillary defect. Issue 1 (January 2016) - Yu, Miao; Qin, Xing-jun; Zhang, Chen-ping; Xu, Li-qun
Abstract: Total maxillary defects with orbital retention (Brown class 2b) are a challenge to reconstructive surgeons because of the variety of anatomical structures involved. Traditional techniques to reconstruct the orbital floor, zygoma, and maxilla using only a vascularised fibular flap are complicated, as the osteotomy and orientation of bone are difficult. Reconstruction of the orbital floor with titanium mesh may also cause palpable discomfort and increase the risk of secondary infection. We describe a modified technique using a vascularised fibular flap, together with a coronoid temporalis pedicle flap, which we used in two patients in whom we achieved satisfactory aesthetic and functional results. Our technique provides adequate tissue for infraorbital skin defects, provides pedicles of sufficient length, and requires only one fibular osteotomy. To our knowledge this is the first report of this technique.